The continuum of maternal sepsis severity: incidence and risk factors in a population-based cohort study. - Colleen D Acosta; Marian Knight; Henry C Lee; Jennifer J Kurinczuk; Jeffrey B Gould; Audrey Lyndon (PLoS ONE)
Objective To investigate the incidence and risk factors associated with uncomplicated maternal sepsis and progression to severe sepsis in a large population-based birth cohort. Methods This retrospective cohort study used linked hospital discharge and vital statistics records data for 1,622,474 live births in California during 2005-2007. Demographic and clinical factors were adjusted using multivariable logistic regression with robust standard errors. Results 1598 mothers developed sepsis; incidence of all sepsis was 10 per 10,000 live births (95% CI = 9.4-10.3). Women had significantly increased adjusted odds (aOR) of developing sepsis if they were older (25-34 years: aOR = 1.29; ≥35 years: aOR = 1.41), had ≤high-school education (aOR = 1.63), public/no-insurance (aOR = 1.22) or a cesarean section (primary: aOR = 1.99; repeat: aOR = 1.25). 791 women progressed to severe sepsis; incidence of severe sepsis was 4.9 per 10,000 live births (95% CI = 4.5-5.2). Women had significantly increased adjusted odds of progressing to severe sepsis if they were Black (aOR = 2.09), Asian (aOR = 1.59), Hispanic (aOR = 1.42), had public/no-insurance (aOR = 1.52), delivered in hospitals with <1,000 births/year (aOR = 1.93), were primiparous (aOR = 2.03), had a multiple birth (aOR = 3.5), diabetes (aOR = 1.47), or chronic hypertension (aOR = 8.51). Preeclampsia and postpartum hemorrhage were also significantly associated with progression to severe sepsis (aOR = 3.72; aOR = 4.18). For every cumulative factor, risk of uncomplicated sepsis increased by 25% (95% CI = 17.4-32.3) and risk of progression to severe sepsis/septic shock increased by 57% (95% CI = 40.8-74.4). Conclusions The rate of severe sepsis was approximately twice the 1991-2003 national estimate. Risk factors identified are relevant to obstetric practice given their cumulative risk effect and the apparent increase in severe sepsis incidence.